Hubungan Indeks Massa Tubuh dan Aktivitas Fisik dengan Keluhan Low Back Pain pada Mahasiswa Kedokteran di Jawa Barat - Alya Kamila Ramadhanty; Titik Respati; Dony Septriana Rosady (Bandung Conference Series: Medical Science, 2022)
Abstract. Low Back Pain (LBP) is a significant health problem because it can cause disability and impaired quality of life. Medical students have a demanding curriculum that can lead to a sedentary lifestyle. This study was conducted to determine the relationship between body mass index and physical activity with complaints of low back pain in medical students in West Java. The research method used is observational analytic with a cross-sectional approach. Data were obtained through questionnaires using snowball sampling. Data was collected in September–November 2021. Data processing used SPSS version 23 and statistical analysis using the chi-square test. The results showed body mass index mostly normal (45.1%), physical activity mostly sedentary (64.8%), and complaints of low back pain as much as 76.9%. The results of the statistical test showed body mass index and physical activity with complaints of low back pain (p=0.715 and 0.854 respectively). This study concludes that there is no correlation between body mass index and physical activity with the complaints of low back pain. Abstrak. Low Back Pain (LBP) merupakan masalah kesehatan yang sangat penting, karena dapat menyebabkan disabilitas dan gangguan kualitas hidup. Mahasiswa kedokteran memiliki kurikulum yang padat sehingga dapat mengarah pada sedentary lifestyle. Penelitian ini dilakukan untuk mengetahui hubungan indeks massa tubuh dan aktivitas fisik dengan keluhan low back pain pada mahasiswa fakultas kedokteran di Jawa Barat. Metode penelitian yang digunakan yaitu analitik observasional dengan pendekatan cross sectional. Data diperoleh melalui kuesioner, dengan cara snowball sampling. Pengambilan data dilakukan pada bulan September–November 2021. Pengolahan data menggunakan SPSS versi 23 dan analisis statistik menggunakan uji chi-square. Hasil penelitian menunjukkan indeks massa tubuh sebagian besar normal (45,1%), aktivitas fisik sebagian besar ringan (64,8%) dan keluhan low back pain sebanyak 76,9%. Hasil uji statistik indeks massa tubuh dan aktivitas fisik dengan keluhan low back pain (p=0,715 dan 0,854). Simpulan penelitian ini, tidak terdapat hubungan antara indeks massa tubuh dan aktivitas fisik dengan keluhan low back pain.